Union-nonunion wage gap: Some unexpected findings in Brazilian labour market - André Gambier Campos; Ana Carolina Moura (Institute for Applied Economic Research (ipea), 2017)
This paper presents new empirical evidence about the wage gap between union and nonunion workers in Brazil. In principle, due to the rules governing union organization/mobilization, no one should rationally expect such gap. However, as this paper reveals, there is empirical evidence of its existence in the labour market. Furthermore, this wage gap may increase in the future, depending on how the labour reform conducted through the Bill n. 6.787/2016 (under discussion in the Parliament) may be implemented.
Keywords: J00; J31; J51; 330; unions; collective bargaining; wages